Mature open cows are rarely persistently infected with bovine viral diarrhea virus - White, Bradley J.; Larson, Robert L.; Thomson, Daniel U. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Bovine viral diarrhea virus (BVDv) is an immunosuppressive virus affecting cattle in a multitude of ways. The varied presentation makes this disease difficult to identify in cow herds and the signs of a BVD infection may be very subtle. The syndrome causes economic problems by reducing herd fertility and increasing disease rates. The persistently infected (PI) animal is a unique reservoir for BVDv. These cattle are the result of in utero exposure to the noncytopathic biotype of BVDv prior to the development of a competent fetal immune system at about 125 days of gestation. Persistently infected animals are the primary method for the disease to propagate over time. PI cattle consistently shed BVD virus in relatively high levels and this exposure to the breeding herd can result in new PI calves. PI animals propagate BVDv in the herd and decrease pregnancy percentages compared to herds without PI animals. Farms must assess risk and manage for biosecurity when purchasing adult animals with an unknown history of disease exposure. Breeding herds that introduce new animals to the herd face the risk of importing a BVD PI animal. To mitigate this risk, PI animals must be accurately identified prior to herd introduction, but visual appraisal is not an accurate method of discovering these animals. Multiple diagnostic tests are available to determine the BVD status of incoming animals and all have an associated cost. Economic feasibility of determining the BVD PI status of animals depends to a large degree on the frequency with which PI animals occur in a population. Previous research has illustrated that PI calves entering the feedyard phase of production are fairly rare (about three per 1,000 calves); however, very little work has been done in mature animals. This project provides an estimate of BVD PI frequency for a specific population. This assessment should allow the formulation of a BVD-specific risk management plan which addresses the economic efficiency of testing mature females upon arrival. The primary objective of this research is to determine the prevalence of BVD PI animals in a population of young (3- to 6-year-old) cows purchased as non-pregnant mature animals. The results can guide biosecurity decisions for producers when purchasing and introducing this class of animal to the herd.
Keywords: Beef; Cattle; Bovine viral diarrhea virus (BVDv); persistently infected (PI)